2019
DOI: 10.3847/1538-4357/ab14e6
|View full text |Cite
|
Sign up to set email alerts
|

Do Kepler Superflare Stars Really Include Slowly Rotating Sun-like Stars?—Results Using APO 3.5 m Telescope Spectroscopic Observations and Gaia-DR2 Data

Abstract: We report the latest view of Kepler solar-type (G-type main-sequence) superflare stars, including recent updates with Apache Point Observatory (APO) 3.5 m telescope spectroscopic observations and Gaia-DR2 data. First, we newly conducted APO 3.5 m spectroscopic observations of 18 superflare stars found from Kepler 1-minute time-cadence data. More than half (43 stars) are confirmed to be “single” stars, among 64 superflare stars in total that have been spectroscopically investigated so far in this APO 3.5 m and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
226
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(263 citation statements)
references
References 129 publications
22
226
1
1
Order By: Relevance
“…One result of the analysis of the photometric data collected in the main Kepler mission was the detection of superflares on solar-type (G-type main-sequence) stars (e.g., Maehara et al 2012. Superflares with energy up to 10 35 erg also occur on slowly rotating stars (e.g., Kitze et al 2014, Notsu et al 2019). However, the frequency for superflares on these slow rotators is very low compared with rapidly rotating stars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One result of the analysis of the photometric data collected in the main Kepler mission was the detection of superflares on solar-type (G-type main-sequence) stars (e.g., Maehara et al 2012. Superflares with energy up to 10 35 erg also occur on slowly rotating stars (e.g., Kitze et al 2014, Notsu et al 2019). However, the frequency for superflares on these slow rotators is very low compared with rapidly rotating stars.…”
Section: Discussionmentioning
confidence: 99%
“…This finding confirms the results of S16, which was based on long-cadence LCs. Notsu et al (2019) found a correlation between amplitude of spot modulation and the occurrence rate of superflares in solarlike stars. They concluded that the majority of these strongest flares occur on stars with large spots.…”
Section: Flaresmentioning
confidence: 92%
See 1 more Smart Citation
“…In order to determine the starspot area we will look to use the method described by Notsu et al (2019). Firstly we must estimate the temperature of the spot which can be done by applying a relation on the difference between the photosphere and the spot.…”
Section: Starspot Areasmentioning
confidence: 99%
“…More recently, Notsu et al (2019) presented a complete review of Kepler solar-type superflares including updates on a new sample using the Apache Point Observatory (APO) and Gaia DR2. The results from Gaia DR2 revealed the possibility of contamination of subgiant stars within the classification of Kepler solar-type stars.…”
Section: Introductionmentioning
confidence: 99%